Architectural And Design Concept In The Historical Museum National - Awaloedin, Dipa Teruna; Pradini, Gagih; Maramis, Henson Palmer; Alkaf, Muhammad Syafiquraman; Erianie, Vannesha; Andini, Davi Ayu (CV ODIS, 2024)
The National History Museum (MSN), situated beneath the National Monument in Jakarta, is a vital cultural institution displaying 51 dioramas depicting Indonesia's history. This research, utilizing qualitative methods and SWOT analysis, explores the museum's architecture, historical representation, and strategic positioning. The results highlight the integration with the monument, the use of marble, and the significance of the Independence Space. The SWOT analysis identifies strengths (cultural heritage), weaknesses (limited amenities), opportunities (increased interest), and threats (competition and potential damage). The study concludes that developing MSN as a tourist destination is crucial, suggesting comprehensive research, optimized asset utilization, and alternative promotional strategies for increased visitation.